HUMAN DEVELOPMENT PERFORMANCE PROFILE DAN KORELASINYA DENGAN PRODUKTIVITAS TENAGA KERJA DI INDONESIA - Zainul Bahri Dalimunthe (Universitas Trisakti, 2005)
The result of research, found out that during the period of 1990- 1996, in every province in Indonesia, Human Development Index (HDI), Gender-Related Development Index (GDI), and Gender Empowerment Measure (GEM) are going up and Human Poverty Index (HPI) is down significantly and human development in Indonesia is getting better. There is a significant and linear correlation between human development performance profile and labor force productivity in Indonesia in 1996 and classified into moderatelly high correlation.Then the use of composite index like HDI, GDI, GEM, and HPI reflecting the complex reality is considered very important Evaluation for improvement and development is still required. Subsequent research revise and improve the methodology of composite index and its indicators.